Long-term consequences of traumatic brain injuries with ice-hockey players - Sekretnyi, Volodymyr; Nekhanevych, Oleh (Journal of Education, Health and Sport, 2021)
Introduction Significant part of sports related concussions (SRC) are below the level of clinical diagnosis of SRC or are unnoticed. The most severe cumulative consequence of SRC is chronic traumatic encephalopathy (CTE). The study of a wide range of clinical manifestations of CTE plays an important role. Purpose To establish long-term cognitive consequences of TBI in ice hockey players. Material and methods Retrospectively, we tested retired 20 ice hockey players. All athletes completed a questionnaire with their team doctor, which included: passport part, sports history, history of SRC, a mini mental scale evaluation (MMSE) and «the clock drawing test». Results The results of the analysis showed a statistically significant decrease in the value of MMSE with an increase in SRC more than 1 during a sports career. Thus, in the group with 1 SRC the value of MMSE was 28.7 (1.38) points, while in the group with 2 or more SMS it was equal to 26.7 (1.15) points (p <0.05). MMSE goalkeepers scored 26.6 (0.6) points, strikers – 27.8 (0.4) points, defenders – 28.2 (0.7) points (p<0.05). The fact of hospitalization indicates clinically significant severity of a history of SRC. Having retrospectively collected data on hospitalization of hockey players after SRC, there was also a decrease in the value of MMSE in those with a history of hospitalization. Thus, in the group of people with hospitalization MMSE was 27.1 (1.39) points, without hospitalization – 27.9 (1.7). No statistically relationship between age and severity of cognitive impairment was found. Significant statistic connection (n = 20, correlation coefficient rs = – 0.40; p<0.05) has been found between the number of SRC and the indicator and MMSE test and between number of SRC and «the clock drawing test» (n = 20, correlation coefficient rs = – 0.10; p <0.05). Conclusions Our study has outlined connection between cognitive impairment in ice-hockey players and SRC.